Dynamic modeling of an open cathode PEM fuel cell for automotive energy management applications - Nada Rifai; Jalal Sabor; Chakib Alaoui; Raffaele Petrone; Hamid Gualous (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Among the different clean energy conversion devices, fuel cells systems are largely employed due to their high-power densities and efficiencies. Several models are available in literature to characterize their functioning, both for stationary and dynamic behaviors. Vehicular application of a fuel cell requires a model that is accurate enough, and simple enough for quick computations for real-time reporting. To meet these constraints, the model of the different sources must be simple and efficient as they are used in the energy management strategy block to estimate the power references to be requested from the sources. The objective of this paper is then to develop a fuel cell model that is both efficient at representing the dynamic and static behavior of the fuel cell, and low consuming in terms of storage space and computation time. The aim is to have a suitable model for use in online simulations for vehicle energy management applications. The proposed model is compared to a representative dynamic model, and the results approve the performance of the model. An experimental test bench is performed to evaluate and validate the proposed model. The model shows good agreement with the experimental data.